(untitled) (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Commonly herniotomy and hernioplasty is performed under subarachnoid block (SAB). In this report we describe the anesthetic management of a patient with moderately decreased cardiac function who underwent herniotomy and hernioplasty under lumber epidural anesthesia. To the best of our knowledge this case is one of the few literature which describe epidural anesthesia for herniotomy and hernioplasty in a cardiac compromised patient. DOI: http://dx.doi.org/10.3329/jbsa.v24i2.19806 Journal of Bangladesh Society of Anaesthesiologists 2011; 24(2): 77-78